1965
DOI: 10.1107/s0365110x65000610
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the intermetallic phase FeAl6

Abstract: The structure of FeA1 e has been refined. The unit cell is orthorhombic and the structure is isostructural with MnA16 and with a-FeCuA1, which is a copper-stabilized form of FeAle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…However, due to its low solubility in Al, Fe may be present as secondary phases in the form of intermetallics. [6][7][8][9][10][11][12] Although it has been demonstrated that these particles can strengthen and increase the temperature resistance with little increase in weight, an effective use of Fe as a major alloying element in structural alloys of Al has not been possible to date. The secondary phases cannot be manipulated easily through conventional deformation and heat treatment including supersaturation and subsequent aging for fine precipitation.…”
Section: Introductionmentioning
confidence: 98%
“…However, due to its low solubility in Al, Fe may be present as secondary phases in the form of intermetallics. [6][7][8][9][10][11][12] Although it has been demonstrated that these particles can strengthen and increase the temperature resistance with little increase in weight, an effective use of Fe as a major alloying element in structural alloys of Al has not been possible to date. The secondary phases cannot be manipulated easily through conventional deformation and heat treatment including supersaturation and subsequent aging for fine precipitation.…”
Section: Introductionmentioning
confidence: 98%
“…[6] Several studies by other workers, [7,8,9] have focused upon the Al-rich part of the system, where the u-Al 3 Fe, a-AlFeSi, and b-AlFeSi phases have been reported as equilibrium phases. [9,10] In addition, some nonequilibrium phases have been identified, for example, metastable phases such as Al 6 Fe, [3,11,12] Al m Fe, [13,14] and Al x Fe [3,15] instead of the u-Al 3 Fe (or u-Al 13 Fe 4 ) [16,17] equilibrium phase. Structures of various phases, e.g., Al 6 Fe, [13,18] Al 3 Fe, [11,19] and a-AlFeSi [20,21,22] have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of Al 3 Fe seems to be easy in comparison with that of Al 6 Fe from the view point of orientation relationships. However, the monoclinic crystal structure of the Al 3 Fe, composed of 102 atoms in a unit cell, 12) is very complicated, whereas crystal structure of the Al 6 Fe, orthorhombic with 28 atoms in a unit cell, 13) is relatively simple. Moreover, the atomic volume of the Al 3 Fe phase is about 0.0191 nm 3 , larger than that of Al 6 Fe, about 0.0176 nm 3 .…”
Section: Precipitation Sequencementioning
confidence: 99%
“…The bright field image (c) was taken by tilting the specimen in order to show the precipitate clearly. The SADP can be indexed as the matrix and the metastable precipitate Al 6 Fe (orthorhombic, a 0 ¼ 0:6464, b 0 ¼ 0:7440, c 0 ¼ 0:8779 nm 13) ). However, it is necessary to take such diffraction pattern which composes of low index planes in order to distinguish Al 6 Fe from Al 3 Fe, because the lattice parameters in both phases are too large.…”
Section: )mentioning
confidence: 99%